A compilation of metamorphic pressure–temperature estimates from the Svecofennian province of eastern and central Sweden. (2nd January 2018) - Skelton, Alasdair; Mansfeld, Joakim; Ahlin, Stellan; Lundqvist, Thomas; Linde, Josefin; Nilsson, Jonas
Abstract: Here, we present a compilation of 44 metamorphic pressure–temperature (P–T) estimates from 31 localities in the Svecofennian province of eastern and central Sweden. Based on these P–T estimates, which were obtained using the average P–T method of the computer programme THERMOCALC, we calculated an apparent metamorphic field gradient of 54 ± 4 °C/km for the Svecofennian province. This is typical for low-medium P/T (Buchan) metamorphism and supports tectonic models that imply Svecofennian crustal growth by accretion of volcanic arc systems. In general, estimated P and T conditions range from 0.2 to 0.6 GPa and from 400 to 800 °C, respectively; i.e., from greenschist to granulite facies conditions. Metamorphic grade is generally higher, reaching upper amphibolite or granulite facies in northern and southwestern parts of the Svecofennian province, whereas metamorphism in Bergslagen was at greenschist to lower amphibolite facies conditions. The higher metamorphic temperatures recorded by rocks in the southwestern part of the province might relate to magmatic activity associated with the Transscandinavian Igneous Belt (TIB). Higher pressure, epidote amphibolite facies metamorphic conditions in the western part of the province probably reflect Sveconorwegian overprinting. Finally, local upper amphibolite and granulite facies conditions probably reflect contact metamorphism.